Analisis Penguatan Hubungan Qatar-Turki Selama Krisis Teluk 2017 - Fatunnisa, Hani (Center for Integrative International Studies Laboratory, Faculty of Political and Social Sciences, UIN Sunan Ampel Surabaya, 2020)
The Gulf coalition country led by Saudi Arabia simultaneously severed its diplomatic relations with Qatar in early June 2017. This action was motivated by Saudi Arabia's accusations of Qatar's proximity to several Islamic opposition organizations such as the Muslim Brotherhood and Hamas and its bilateral tendencies with Iran. This resentment continued with the launching of a land, sea and air blockade against Qatar's territory. Qatar dismissed the accusations and saw the Arab coalition's actions as an intervention against its foreign policy. In addition, Turkey as an ally of Qatar initially responded to the diplomatic crisis in a neutral manner and put forward mediation efforts. However, these efforts failed due to sabotage by the Gulf coalition. Turkey later denounced the blockade and immediately signed a military agreement to speed up the deployment of troops to Qatar. This article aims to analyze the reasons for Turkey's shift from initially neutral to pro-Qatar by strengthening its bilateral relations with Qatar through a series of help.